LSLC-BASED GUIDED DISCOVERY LEARNING MODEL ON LEARNING OUTCOMES OF ELECTROLYTE AND NON-ELECTROLYTE SOLUTIONS - Ladisa Fergie Imanah; Yerimadesi Yerimadesi; Andromeda Andromeda (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2022)
The purpose of this study is to analyze the influence of the application of guided discovery learning models based on lesson study for community learning on student learning outcomes. The type of research that pseudo-experiments use with research design is pretest-postest control group design. The population consists of students of class X MIPA at public high school 1 Padang. Sample selection is carried out by random sampling techniques, and selected sample classes, namely X MIPA 1 and X MIPA 4. The instrument used in this study is a test instrument in the form of multiple choice questions consisting of 20 questions with 5 answer options. Data analysis techniques use n-gain tests, normality tests, F tests and hypothesis tests (t tests). The average learning outcomes of students of the experiment and control classes were 81, and 72, respectively,.The level of influence of LSLC-based guided discovery learning models is analyzed through n-gain test scores. From the results of the study obtained an n-gain score in the experimental class of 0.74 with a high category while the control class was 0.61 with a medium category. At the significance level of 0.05 indicates the value of tcount (2.746) > ttable (1.995). So that the implementation of a guided discovery learning model based on lesson study for community learning has a problem with improving student learning outcomes